PENGARUH MOTIVASI WIRAUSAHA DAN KOMPETENSI WIRAUSAHA TERHADAP KEBERHASILAN USAHA TEKSTIL DI PUSAT PASAR MEDAN - Situmorang, Irvan Rolyesh (NIAGAWAN, 2024)
This research aims to determine the influence of entrepreneurial motivation and entrepreneurial competence, both partially and simultaneously, on the success of textile businesses in the Medan Market Center. The research methodology used is a quantitative-descriptive method. The respondents who will be studied in this research are textile business actors in the Medan market center. This research uses a saturated sample, which means the population is used as a sample, and researchers will take 52 textile business actors in the market center. The research results show that entrepreneurial motivation and entrepreneurial competence have a significant effect on the success of textile businesses in the Medan market center. The research results also show that entrepreneurial motivation and entrepreneurial competence simultaneously influence the success of textile businesses in the Medan market center. The results of the coefficient of determination test show that entrepreneurial motivation and entrepreneurial competence can provide a percentage contribution to the success of textile businesses in the Medan market center